Biomechanics of different thread designs of dental implants assisting unilateral free end mandibular partial dentures - Bandar Awadh Alresheedi; Ali Alenezi; Naji Alharethi; Abeer Mohamed Ettesh; Mohamed Ahmed Alkhodary (BMC Oral Health)
Abstract Background Dental implants assisting unilateral free end mandibular partial dentures (RPDs) improve their performance and prognosis, however, no consensus exists on the type of thread used in these implants. The current work studied the effect of dental implant thread design on stress distribution around dental implants assisting unilateral free end RPDs using strain gauges and finite element analysis to select the best performing thread design. Methods Twenty-four custom made titanium-aluminum-vanadium (Ti-6Al-4 V) implants were designed and milled 4 thread designs; V-shaped, buttress, reverse-buttress and trapezoid, and were inserted in the approximate locations of tooth number 36 in 6 polymethyl methacrylate Class II Kennedy models, which had teeth number 36, 37, and 38 missing, and unilateral removable partial dentures were constructed to fit each model, with a metal housings and O-rings in their fitting surface attaching to the ball abutment. Surface strains were measured with strain gauges, and mean stresses around the implants, and principal abutments in each tested model were compared using one way analysis of variance (ANOVA). The finite element analysis, recorded stresses, around each dental implant thread design, in the form of colorcoded maps using Von Mises stress analysis. Results The recorded micro-strains around V-shaped threads and their related abutments were higher than those recorded around the buttress threads and their related abutments, reverse buttress threads and their related abutments, and trapezoid threads and their related abutments in descending order as determined by one‑way ANOVA (F = 284.489, p < 0.001), and Tukey post hoc pairwise comparison (p < 0.001). FEA results presented the stresses generated around each thread design, under vertical load, the highest stress concentration values were observed around V-shaped threads, followed by the buttress threads, the reverse buttress threads, and finally the least stresses were observed around the trapezoid threads. Under oblique load, more stresses were observed than those under vertical load, being also greatest around V-shaped threads, then decreasing around buttress, reverse buttress, and trapezoid threads. Conclusions The strain gauge and finite element analysis revealed that the trapezoid threads demonstrated least stress concentration at the bone implant interface, followed by the reverse buttress, buttress, and finally the V-shaped threads.